A23 CIRCULATING PROPIONATE AND SPLANCHNIC VASODILATION IN CIRRHOSIS. (1st March 2018) - McDougall, C; Davila, A; Mason, A; Alghbli, S; Hojanepesov, O; Shah, D; Mason, A; Tandon, P; Abraldes, J
Abstract: Background: Splanchnic arterial vasodilation is at the center of the pathogenesis of cirrhosis complications since it contributes to portal hypertension and arterial hypotension. The mechanisms of vasodilation in cirrhosis are still not well understood which results in lack of targeted pharmacological therapies. Recently it has been shown in experimental animals that gut derived short chain fatty acids, in particular propionate, have vasoactive properties causing vasodilation. Aims: Our aim was to assess if propionate contributes to splanchnic vasodilation in cirrhosis. Methods: In 42 patients with cirrhosis (Child-Pugh A/B/C: 10/18/14) and portal hypertension we analysed plasma levels of propionate (LC-MS), HVPG and the transcriptome of liver biopsies. In sham-operated rats and rats with biliary cirrhosis (4 weeks of common bile duct ligation or CBDL), we assessed circulating propionate levels, and the hemodynamic effects of a continuous infusion of propionate (vs saline) on portal pressure (PP), mean arterial pressure (MAP) and superior mesenteric artery blood flow (SMABF, as a readout of splanchnic vasodilation). Results: Cirrhosis patients showed increased circulating propionate above normal laboratory values that correlated with the degree of portal hypertension (p=0.004; Fig 1) and a downregulation of the metabolic pathway of propionate (FDR<0.000001). We then assessed in control (sham-operated) rats the effects of an infusion causing increase in propionate levels comparable to that observed in advanced cirrhosis. Propionate infusion caused an increase in SMABF (+64%, p<0.05) and hypotension (-12%, p<0.05), ) without significantly modifying portal pressure (+6%, ns). Cirrhotic rats (CBDL) showed a 1.9 fold increase in propionate levels as compared to sham rats (p=0.047), that correlated with MAP (p<0.05), and a significant downregulation of liver propionate metabolic pathway (FDR<0.001). In cirrhotic rats propionate infusion induced a further worsening in cirrhosis hemodynamics, causing further decrease in MAP (-15%, p<0.05), increased SMABF (+48%, p<0.05) an increase in portal pressure (+14%, p<0.05). Conclusions: Propionate is increased in cirrhosis and correlates with the degree of portal hypertension. In rats an increase in circulating propionate induces hypotension, increases SMABF and, in cirrhotic rats, aggravates portal hypertension. Altogether this suggests that propionate contributes to the abnormal hemodynamics of advanced cirrhosis and might be an actionable target to improve arterial hypotension and portal hypertension in these patients. Funding Agencies: American Gastroenterological Association